High Antigen Dose Is Detrimental to Post-Exposure Vaccine Protection against Tuberculosis - Billeskov, Rolf; Lindenstrøm, Thomas; Woodworth, Joshua; Vilaplana, Cristina; Cardona, Pere-Joan; Cassidy, Joseph P.; Mortensen, Rasmus; Agger, Else Marie; Andersen, Peter (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis (Mtb), the etiologic agent of tuberculosis (TB), causes 1.8M deaths annually. The current vaccine, BCG, has failed to eradicate TB leaving 25% of the world’s population with latent TB infection (LTBI), and 5-10% of these people will reactivate and develop active TB. An efficient therapeutic vaccine targeting LTBI could have an enormous impact on global TB incidence. Here we show in a mouse model that post exposure, but not preventive, vaccine protection requires low vaccine antigen doses for optimal protection. Loss of protection from high dose post-exposure vaccination was associated not with a loss of overall vaccine response magnitude, but rather with greater differentiation and lower functional avidity of vaccine specific CD4 T cells. These results underscore the importance of T cell quality rather than magnitude in TB-vaccine protection.